Correlations of Prostate Volume with PSA Levels in BPH Patients at Ulin General Hospital Banjarmasin - Nur Ramadhanti Cindy Levissa; Eka Yudha Rahman; Dewi Indah Noviana Pratiwi; Heru Prasetya; Siti Kaidah (Berkala Kedokteran, 2021)
Abstract: This study aims to determine the association between prostate volume and PSA levels in BPH patients at Ulin Hospital Banjarmasin. This study used a cross-sectional retrospective approach and analytic method. A total of 52 samples were obtained by purposive sampling based on inclusion and exclusion criterias. The highest prostate volume of  20.00-39.99 cc was obtained from 16 patients (30.7%) and the lowest volume of  60.00-79.99 cc was obtained from 10 patients (19.2%). Examination of PSA levels were highest at 2.6-9.9 ng/mL from 24 patients (46.2%) and the lowest at >20.0 ng/mL (5.8%) from 3 patients. Data analysis using Pearson correlation coefficient showed a positive correlation between prostate volume and PSA levels in BPH patients at Ulin Hospital Banjarmasin with a p value = 0,000 and r = 0.616 (positive and strong correlation). Keywords: BPH, Prostate volume, PSA